Room Temperature in Situ Chemical Synthesis of Fe3O4/Graphene - Teo, P.S.; Lim, H.N.; Huang, N.M.; Chia, C.H.; Harrison, I. (Elsevier, 2012)
A simple, cost-effective, efficient, and green approach to synthesize iron oxideigraphene (Fe3O4/rGO) nanocomposite using in situ deposition of Fe3O4 nanoparticles on reduced graphene oxide (rGO) sheets is reported. In the redox reaction, the oxidation state of iron(II) is increased to iron(III) while the graphene oxide (GO) is reduced to rGO. The GO peak is not observed in the X-ray diffraction (XRD) pattern of the nanocomposite, thus providing evidence for the reduction of the GO. The XRD spectra do have peaks that can be attributed to cubic Fe3O4. The field emission scanning electron microscopy (FESEM) images show Fe3O4 nanoparticles uniformly decorating rGO sheets. At a low concentration of Fe2+, there is a significant increase in the intensity of the FESEM images of the resulting rGO sheets. Elemental mapping using energy dispersive X-ray (EDX) analysis shows that these areas have a significant Fe concentration, but no morphological structure could be identified in the image. When the concentration of Fe2+ is increased, the Fe3O4 nanoparticles are formed on the rGO sheets. Separation of the Fe3O4/rGO nanocomposite from the solution could be achieved by applying an external magnetic field, thus demonstrating the magnetic properties of the nanocomposite. The Fe3O4 particle size, magnetic properties, and dispersibility of the nanocomposite could be altered by adjusting the weight ratio of GO to Fe2+ in the starting material.